Omalizumab normalizes the gene expression signature of lesional skin in patients with chronic spontaneous urticaria: A randomized, double‐blind, placebo‐controlled study. Issue 1 (15th October 2018) - Metz, Martin; Torene, Rebecca; Kaiser, Sergio; Beste, Michael T.; Staubach, Petra; Bauer, Andrea; Brehler, Randolf; Gericke, Janine; Letzkus, Martin; Hartmann, Nicole; Erpenbeck, Veit J.; Maurer, Marcus
Abstract: Background: Omalizumab, a humanized recombinant monoclonal anti‐IgE antibody, proved to be effective in patients with chronic spontaneous urticaria (CSU), including severe and treatment‐refractory CSU. Here, we report omalizumab's effect on gene expression in skin biopsies from CSU patients enrolled in a double‐blind, placebo‐controlled study. Methods: Chronic spontaneous urticaria patients (18‐75 years) were randomized to either 300 mg omalizumab (n = 20) or placebo (n = 10) administered s.c. every 4 weeks for 12 weeks (NCT01599637). Lesional and nonlesional skin biopsies were collected from the same area of consenting patients and assessed at baseline and on Day 85 compared with skin biopsies from the same area of 10 untreated healthy volunteers (HVs). Gene expression data were generated using Affymetrix HG‐U133Plus2.0 microarrays. Statistical analyses were performed using R packages. Results: At baseline, 63 transcripts were differentially expressed between lesional and nonlesional skin. Two‐thirds of these lesional signatures were also differentially expressed between lesional and HV skin. Upon treatment with omalizumab, >75% of lesional signatures changed to reflect nonlesional skin expression levels (different vs placebo, P < 0.01). Transcripts upregulated in lesional skin (vs nonlesional and/or HV skin) suggested increased mast cell/leukocyte infiltration (FCER1G, C3AR1, CD93, S100A8, and S100A9), increased oxidative stress, vascularization (CYR61), and skin repair events (KRT6A, KRT16). Lesional signatures were not modulated by treatment in nonresponders (defined based on UAS7 longitudinal changes ≥16). Conclusion: Omalizumab, in treatment responders, reverted transcriptional signatures associated with CSU lesion phenotype to reflect nonlesional/HV expression levels; this is consistent with observed omalizumab‐mediated clinical improvement observed in patients with CSU. Abstract : The gene expression of the lesional skin of patients with chronic spontaneous urticaria shows a distinct signature when compared to their nonlesional skin and the skin of healthy volunteers. The pattern of gene expression in the lesional skin of omalizumab‐treated patients are different than before treatment, but not in their nonlesional skin. In treatment responders, omalizumab treatment shows reverted transcriptional signatures associated with CSU lesion phenotype to reflect nonlesional/healthy volunteer expression levels consistent with observed clinical improvement.